Recorrências: Conceitos e Aplicações - Simões, Diêgo Ayllo da Silva (2014)
In this thesis, we will see theories and problems of linear recurrences. We start with recurrences of rst and second order, some applications and then we see some generalizations to higher order. We also studied operators and generators functions to represent recursion and applications of the Arithmetic recurrences.